PREVALENCE OF AVIAN INFLUENZA SUBTYPE H9N2 IN BACKYARD POULTRY IN AND AROUND BAHAWALPUR CITY - K. Khan; T. Yaqub; M. Z. Shabbir; A. Aslam (Journal of Animal and Plant Sciences, 2021)
Avian influenza subtype H9N2 is endemic in Eurasia and responsible for huge economic losses to the poultry industry. Backyard poultry especially in the areas where modern poultry farming is less common provides a biological niche for the persistence and evolution of Influenza viruses. Current study was designed to bridge this gap by studying the prevalence of H9N2 in backyard poultry in the Bahawalpur city. Out of the ten randomly selected sites in and around the city, only one site was positive for H9N2 virus. The positive site had 22.22% (20/90) prevalence and the overall prevalence rate of the Bahawalpur city was 4% (20/500). This provides a space for viral existence as well as mutation in the viral genome. Backyard poultry sector has close interaction with humans; therefore, Avian Influenza is a continuous threat to humans as a zoonotic agent.
Keywords: Avian Influenza H9N2; Bahawalpur; Prevalence; Backyard Poultry